Teatre, cinema i televisió. L’ús del diàleg - Sirera, Rodolf (Caplletra. Revista Internacional de Filologia, 2002)
The author looks into the common elements in the format-related writing and attends to the pragmatic signs of the professionalisation of the script-writing, mainly in such a culture as the Catalan one. The given examples refer to the dialogue’s functions as for the narrative plot construction and the transmission of contents.